MODEL TAFSIR FIQHI: KAJIAN ATAS TAFSîR AL-MUNîR FI AL-‘AQîDAH WA AL-SYARî’AH WA AL-MANHAJ KARYA WAHBAH AZ-ZUHAILI (Mazahib, 2012)
Fiqhi commentary is an attempt interpretation of legal texts. One interpretation is classified as a work of interpretation is fiqhi Tafsir Al-Munir, the greatest work of Az-Zuhaili Wahbah, a contemporary scholar who has a very broad insight. In the work of this interpretation, legal texts are described in the open, in order that people can understand all the issues at hand. The style and method of use has its own characteristics that distinguish it from other works fiqhi interpretation.